2015
DOI: 10.1259/dmfr.20150070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence of FOV sizes and different voxel resolutions for the assessment of periodontal defects

Abstract: Objectives: This study assessed the influence of different voxel resolutions of two different CBCT units on the in vitro detection of periodontal defects. Methods: The study used 12 dry skulls with a maxilla and a mandible. Artificial defects (dehiscence, tunnel, fenestration) were separately created on the anterior, premolar and molar teeth using burrs. A total of 14 dehiscences, 13 fenestrations, 8 tunnels and 16 non-defect controls were used in the study. Images were obtained from two different CBCT units i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 34 publications
0
30
1
4
Order By: Relevance
“…Because the soft tissues with attenuation coefficients may affect the x‐ray beam, it is better to use materials simulating soft tissues to better replicate a live person. Different methods such as putting the ribs in a plastic container filled with water or covering the ribs with double layers of boxing wax were used to stimulate soft tissues. It should be kept in mind that the use of hydrocolloid impression material for soft tissues simulation is not well evaluated; however, because the materials were similar in both groups, the comparison is possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the soft tissues with attenuation coefficients may affect the x‐ray beam, it is better to use materials simulating soft tissues to better replicate a live person. Different methods such as putting the ribs in a plastic container filled with water or covering the ribs with double layers of boxing wax were used to stimulate soft tissues. It should be kept in mind that the use of hydrocolloid impression material for soft tissues simulation is not well evaluated; however, because the materials were similar in both groups, the comparison is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The fenestration defects were prepared 10 mm apically from the superior border of the rib. The cervical and apical sites of each bovine rib were randomly exposed to either fenestration or dehiscence defects . The width and depth of each defect were measured by an electronic digital caliper with small tips and a resolution of 0.01 mm, and the defects larger than 3 mm in each dimension were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced voxel sizes are needed for detecting and measuring periodontal and peri‐implant defects of much smaller dimensions than the post‐extraction alveolar socket assessed in the present study (Pinheiro et al., ). Kolsuz, Bagis, Orhan, Avsever, and Demiralp () identified a voxel size of 0.15 mm as the cutoff point for overall detection of a periodontal bony defect, while Kamburoğlu et al. () identified a voxel size of 0.1 mm for furcation defects.…”
Section: Discussionmentioning
confidence: 99%
“…Kolsuz et al (16) reported that the voxel size of 0.15 mm 3 and less was more accurate than 0.16 mm 3 and 0.20 mm 3 in the detection of periodontal defects. Kolsuz et al (16) reported that the voxel size of 0.15 mm 3 and less was more accurate than 0.16 mm 3 and 0.20 mm 3 in the detection of periodontal defects.…”
Section: Discussionmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT), which provides high-resolution, three-dimensional, highcontrast and clear structural images, can be used to detect ERR effectively (4,11,12). The effect of small voxel size on image quality has been proven in many studies in the literature (13)(14)(15)(16)(17), but no study has been found evaluating the effect of changes in current on the diagnosis of ERR when other parameters remain constant. The quality of the images obtained using CBCT depends on parameters, such as milliampere (mA), kilovoltage and voxel size.…”
Section: Introductionmentioning
confidence: 99%